New separation method for monoclonal immunoradiometric assays and its application to assays for thyrotropin and human choriogonadotropin. - S J Rattle; D R Purnell; Pierre-Marc Williams; Kenneth Siddle; G C Forrest (1984)
Abstract We describe a novel separation procedure for immunoradiometric assays involving monoclonal antibodies in which both radiolabeled and capture antibodies are used in solution, the capture antibody being labeled with fluorescein isothiocyanate (FITC). Separation is achieved by incubation with anti-FITC antibodies on magnetic particles. This technique enhances reaction kinetics relative to those of assays in which a solid-phase capture antibody is used, thus allowing faster reaction times and more economic use of the monoclonal antibodies. The use of anti-FITC magnetic solid phase produces an assay having a highly specific separation method, minimal nonspecific binding, and high sensitivity. The method is illustrated by application to assays for thyrotropin and human choriogonadotropin.